Keeping an eye on the conductor: neural correlates of visuo-motor synchronization and musical experience - Ono, Kentaro; Nakamura, Akinori; Maess, Burkhard (Frontiers in Human Neuroscience, 2015)
For orchestra musicians, synchronized playing under a conductor’s direction is necessary to achieve optimal performance. Previous studies using simple auditory/visual stimuli have reported cortico-subcortical networks underlying synchronization and that training improves the accuracy of synchronization. However, it is unclear whether people who played regularly under a conductor and non-musicians activate the same networks when synchronizing with a conductor’s gestures. We conducted a functional magnetic resonance imaging (fMRI) experiment testing nonmusicians and musicians who regularly play music under a conductor. Participants were required to tap the rhythm they perceived from silent movies displaying either conductor’s gestures or a swinging metronome. Musicians performed tapping under a conductor with more precision than nonmusicians. Results from fMRI measurement showed greater activity in the anterior part of the left superior frontal gyrus (SFG) in musicians with more frequent practice under a conductor. Conversely, tapping with the metronome did not show any difference between musicians and nonmusicians, indicating that the expertize effect in tapping under the conductor does not result in a general increase in tapping performance for musicians. These results suggest that orchestra musicians have developed an advanced ability to predict conductor’s next action from the gestures.